2019
DOI: 10.1016/j.ridd.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Verb production by individuals with Down syndrome during narration

Abstract: Background: Despite research identifying verb knowledge as a strong predictor of later syntactic skills in typical development, virtually no research has examined verb development in Down syndrome. Aims: The purpose of this study was to examine verb production (density, diversity, and typetoken ratios) by individuals with Down syndrome in the context of story generation relative to two comparison groups-nonverbal cognitive ability level matches with typical development and chronological age matches with mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…It is documented that DS individuals produced fewer or no utterances with verbs overall relative to TD population, although this result was found statistically significant only at higher lexical levels (of 251 -400 words) (Galeote et al, 2018). At this point, we should mention that although individuals with DS may have a large number of verbs in their vocabularies, with greater diversity of lexical verbs, however, they did not use them regularly (Loveall et al, 2019). Moreover, they were able to produce transitional forms and made significantly greater use of some of them, for example formulas and dummy element productions, than TDC in some cases (Zampini & D'Odorico, 2011).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…It is documented that DS individuals produced fewer or no utterances with verbs overall relative to TD population, although this result was found statistically significant only at higher lexical levels (of 251 -400 words) (Galeote et al, 2018). At this point, we should mention that although individuals with DS may have a large number of verbs in their vocabularies, with greater diversity of lexical verbs, however, they did not use them regularly (Loveall et al, 2019). Moreover, they were able to produce transitional forms and made significantly greater use of some of them, for example formulas and dummy element productions, than TDC in some cases (Zampini & D'Odorico, 2011).…”
Section: Resultsmentioning
confidence: 79%
“…The data from the studies presented, showed a disadvantage of the DS population in syntactic processing, at both production (Hesketh & Chapman, 1998;Vicari et al, 2000;Ring & Clahsen, 2005a;Tsakiridou, 2006;Joffe & Varlokosta, 2007;Stathopoulou, 2007;Caselli et al, 2008;Zampini & D'Odorico, 2011;Andreou, 2013;Bello et al, 2014;Koizumi et al, 2019;Loveall et al, 2019) and comprehension (Chapman et al, 1991(Chapman et al, , 2002Rondal & Comblain, 1996;Vicari et al, 2000;Perovic, 2001Perovic, , 2006aRing & Clahsen, 2005a, 2005bAndreou, 2013;Bello et al, 2014;Joffe & Varlokosta, 2007;Sanoudaki & Varlokosta, 2014;Loveall et al, 2016;Witecy & Penke, 2017;Polišenská et al, 2018;Koizumi et al, 2019) levels, compared to typically developing individuals. This disadvantage has been interpreted by the researchers as either delayed or following a completely different pathway.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations